1974
DOI: 10.1113/jphysiol.1974.sp010715
|View full text |Cite
|
Sign up to set email alerts
|

The secretion of alkali metal ions by the perfused cat pancreas as influenced by the composition and osmolality of the external environment and by inhibitors of metabolism and Na+, K+‐ATPase activity

Abstract: SUMMARY1. The secretion of sodium, potassium and lithium has been studied in the isolated cat pancreas, perfused with bicarbonate buffered saline solutions of varying composition and osmolality, and stimulated maximally with secretin.2. Under isosmolal conditions, when perfusate sodium chloride was replaced by sucrose, sodium secretion and potassium secretion were directly related to perfusate sodium concentration, [Na] The concentration of potassium in the secretion was almost identical with that in the perfu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
24
0
2

Year Published

1978
1978
1990
1990

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(29 citation statements)
references
References 29 publications
3
24
0
2
Order By: Relevance
“…First, in the present study, ACh-induced secretion of lacrimal gland fluid was inhibited by ouabain, suggesting that the (Na+ + K+)-activated ATPase does play a role in lacrimal gland fluid secretion. This result is in agreement with another study on the lacrimnal gland (Botelho & Fuenmayor, 1981), in which 5 x 10-6 M-ouabain irreversibly inhibited secretion, and with studies on other exocrine glands including the submandibular glands (Petersen & Poulsen, 1967), sweat glands (Sato et al 1969), and pancreas (Case & Scratcherd, 1974).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…First, in the present study, ACh-induced secretion of lacrimal gland fluid was inhibited by ouabain, suggesting that the (Na+ + K+)-activated ATPase does play a role in lacrimal gland fluid secretion. This result is in agreement with another study on the lacrimnal gland (Botelho & Fuenmayor, 1981), in which 5 x 10-6 M-ouabain irreversibly inhibited secretion, and with studies on other exocrine glands including the submandibular glands (Petersen & Poulsen, 1967), sweat glands (Sato et al 1969), and pancreas (Case & Scratcherd, 1974).…”
Section: Discussionsupporting
confidence: 82%
“…Thus, ouabain, a specific inhibitor of (Na+ + K+)-activated ATPase, has been shown to inhibit exocrine gland fluid secretion (Petersen & Poulsen, 1967;Sato, Taylor & Dobson, 1969;Case & Scratcherd, 1974). Since Na+ is the dominant cation in most exocrine secretions, the simplest mechanism by which the (Na+ + K+)-activated ATPase could play a role in secretion would be by actively transporting Na+ from the secretary cells into the glandular lumen.…”
Section: Introductionmentioning
confidence: 99%
“…The very high density of silver grains over the basolateral plasma membranes of the duct cells, combined with the established ouabain sensitivity of pancreatic electrolyte and water secretion (Ridderstap & Bonting, 1969;Case & Scratcherd, 1974), lends strong support to the view that the cells of the duct system play an important role in electrolyte and water secretion. It has previously been demonstrated by micropuncture studies (Schulz, Yamagata & Weske, 1969;Swanson & Solomon, 1973) that the interlobular ducts contribute to pancreatic secretion of electrolytes and water in the rabbit.…”
Section: Discussionmentioning
confidence: 81%
“…The detailed mechanisms of pancreatic secretion ofelectrolytes and water are not very well understood. However, a number of important observations have been made, among which is that ouabain, a specific inhibitor of the (Na+ + K+)-activated ATPase (Glynn, 1964;Skou, 1965), is able to inhibit the secretion of pancreatic juice (Ridderstap & Bonting, 1969;Case & Scratcherd, 1974). Therefore, it can be concluded that the cells which are involved in pancreatic secretion of electrolytes and water must be able to bind [3H]ouabain, and probably to a greater extent than other pancreatic cells.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation